Additive manufacturing for the aerospace industry - Froes, Francis; Boyer, Rodney (Elsevier, 2019)
Additive Manufacturing for the Aerospace Industry explores the design, processing, metallurgy and applications of additive manufacturing (AM) within the aerospace industry. The book's editors have assembled an international team of experts who discuss recent developments and the future prospects of additive manufacturing. The work includes a review of the advantages of AM over conventionally subtractive fabrication, including cost considerations. Microstructures and mechanical properties are also presented, along with examples of components fabricated by AM. Readers will find information on a broad range of materials and processes used in additive manufacturing. It is ideal reading for those in academia, government labs, component fabricators, and research institutes, but will also appeal to all sectors of the aerospace industry.